Rumex induratus leaves: interesting dietary source of potencial bioactive compounds - Ferreres, F. (2010)
The phenolic compounds of Rumex induratus leaves were determined by HPLC-DAD-MS/MS-ESI. The results revealed a profile composed of 19 compounds: caffeoyl-hexoside, two p-coumaroyl-hexoside isomers, feruloyl-hexoside, sinapoyl-hexoside, 6-C-hexosyl-quercetin, 8-C-hexosyl-luteolin, 6-C-hexosyl-luteolin, 6-C-hexosyl-apigenin, 3-O-hexosyl-quercetin, 3-O-rutinosyl-quercetin, 7-O-hexosyl-diosmetin, 3-O-rutinosyl-isorhamnetin, 7-O-(acetyl)-pento-hexosyl-diosmetin, 6-C-hexosyl-genkwanin, and four unidentified O-glycosyl-C-glycosylflavones. The quantification of the identified phenolics by HPLC-DAD showed 6-C-hexosyl-luteolin as the main compound. Organic acid composition was determined by HPLC-UV, revealing a high content of oxalic acid. R. induratus was also investigated for its capacity to act as a scavenger of DPPH and superoxide radicals. Good antioxidative results were obtained against both radicals. Unlike other species of the genus Rumex, R. induratus did not present any anthraquinone derivative.